Antinociceptive and anti-hyperuricemic effects of ethanolic extract from Homalomena pierreana Engl., Araceae - Huong, Nguyen Thi Thu; Chi, Bui Thi Que; Khoi, Cao Dinh; Linh, Nguyen Mai; Han, Tran Hoang Kha (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2024)
Background: Gout is one of arthritis diseases resulting from high levels of plasma uric acid. Screening of medicinal plants for analgesic and anti-hyperuricemic effects is necessary to prevent and treat gout disease. Objectives: Homalomena has been widely used in traditional medicine for the treatment of bone diseases. Homalomena pierreana is a newly discovered rare species found in Vietnam. The study aims to clarify the antinociceptive and anti-hyperuricemic effects of 45% ethanolic extract from H. pierreana rhizome (H. pierreana extract) in male Swiss albino mice. Methods: Acetic acid-induced writhing and thermal stimulus-induced pain (hot plate) assays were applied to investigate antinociceptive effects. Model of potassium oxonate-induced acute hyperuricemia in mice was used to examine anti-hyperuricemic effects. Results: The results revealed that 5-day pretreatment with H. pierreana extract at the oral doses of 390 mg/kg and 780 mg/kg, as well as a reference drug diclofenac sodium, decreased the number of acetic acid-induced writhing in mice. Administration of the extract at doses of 390 mg/kg and 780 mg/kg also significantly delayed the reaction time of mice to pain (or an increase in the latency to licking/jumping) caused by thermal stimulus in hot plate test but the effect was weaker than those of morphine (10 mg/kg, i.p.). Moreover, H. pierreana extract as well as a reference drug allopurinol, significantly reduced plasma uric acid levels of hyperuricemic mice and restored to the baseline levels. Conclusion: H. pierreana extract possesses antinociceptive and anti-hyperuricemic effects which confirm its usefulness of the gout management.